The handbook of transformative learning theory, research, and practice - Taylor, Edward W. (Edward Woodbury), 1952- (Jossey-Bass higher and adult education series., 2012)
"The Handbook of Transformative Learning provides a comprehensive and critical review of more than three decades of theory development, research, and practice in Transformative Learning (TL). It will help adult educators understand what transformative learning is, distinguish it from other forms of learning, and foster it in their practice. The book covers five broad areas: historical, theoretical, practical, research, and future perspective. It is comprehensive, interdisciplinary, critical, reflective, and accessible to a wide audience of interested scholars, students, and practitioners. Co-edited by leading experts in the field with an advisory group of prominent authorities, this handbook is the leading resource for the field"--